2010
DOI: 10.4049/jimmunol.0902221
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid PTEN Promotes Inflammation but Impairs Bactericidal Activities during Murine Pneumococcal Pneumonia

Abstract: Phosphatidylinositol 3-kinase has been described as an essential signaling component involved in the chemotactic cell influx that is required to eliminate pathogens. At the same time, PI3K was reported to modulate the immune response, thus limiting the magnitude of acute inflammation. The precise role of the PI3K pathway and its endogenous antagonist phosphatase and tensin homolog deleted on chromosome 10 (PTEN) during clinically relevant bacterial infections is still poorly understood. Utilizing mice lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 43 publications
9
88
1
Order By: Relevance
“…Genetic evidence, however, suggests that PI3K activation is involved in dampening the proinflammatory profile of both macrophages and dendritic cells (20,21,32). To investigate if BCAP links TLR signaling and PI3K activation, we examined the phosphorylation status of the downstream kinase, Akt, following activation of TLR2, TLR4, and TLR9.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic evidence, however, suggests that PI3K activation is involved in dampening the proinflammatory profile of both macrophages and dendritic cells (20,21,32). To investigate if BCAP links TLR signaling and PI3K activation, we examined the phosphorylation status of the downstream kinase, Akt, following activation of TLR2, TLR4, and TLR9.…”
Section: Resultsmentioning
confidence: 99%
“…60,64,65 Consequently, in a pneumococcal pneumonia model, mice deficient for PTEN in the myeloid compartment have less Tnf, Il6 and Cxcl1 (also known as KC), but more Il10 in their bronchiolar lavage fluid. 66 This phenotype corresponded with increased phagocytosis and elimination of intracellular bacteria by alveolar macrophages infected in vitro with Streptococcus pneumonia. 66 In contrast, Kuroda, et al found a requisite role for PTEN in elimination of Leishmania parasites in vivo in a manner suggested to be dependent upon Tnf-mediated other studies advocated a role for PI3K in inhibiting the inflammatory response.…”
Section: Linking Tlr Signaling To Pi3k Activationmentioning
confidence: 99%
“…66 This phenotype corresponded with increased phagocytosis and elimination of intracellular bacteria by alveolar macrophages infected in vitro with Streptococcus pneumonia. 66 In contrast, Kuroda, et al found a requisite role for PTEN in elimination of Leishmania parasites in vivo in a manner suggested to be dependent upon Tnf-mediated other studies advocated a role for PI3K in inhibiting the inflammatory response. [5][6][7] These discrepancies may be incompletely explained by usage of different pharmacological inhibitors as well as non-standard dosages.…”
Section: Linking Tlr Signaling To Pi3k Activationmentioning
confidence: 99%
“…75 In addition, it can enhance GKS3β activation and thus promote an inflammatory response to TLR agonists in macrophages. 73 Kamo et al 76 found that the knockdown of PTEN could promote AKT/β-catenin/Foxol signaling and could down-regulate TLR4 expression in mouse liver cells responding to ischemia/reperfusion injury. The same signaling pathway may also trigger highmobility group box 1-mediated innate immune response in acute lung injury.…”
Section: Functions Of Pten In Innate Immunity and Antiviral Defensementioning
confidence: 99%
“…Deletion of PTEN in myeloid cells could enhance macrophage phagocytosis, reduce pulmonary neutrophil influx, diminish TNF-α, increase IL-10 and improve survival after S. pneumonia infection. 73 In addition, PTEN acts as an important regulator of NK cell localization. Leong et al found that in an NK cellspecific Pten-deletion mouse model, there was a significant expansion of peripheral blood NK cells and the premature egress of NK cells from the bone marrow due to selective hyper-responsiveness to the blood localizing chemokine sphingosine 1-phosphate.…”
Section: Functions Of Pten In Innate Immunity and Antiviral Defensementioning
confidence: 99%